DETERMINATION OF FACTORS AFFECTING CAPITAL STRUCTURE (EMPIRICAL STUDY ON INDUSTRIAL SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2021-2023) - Adilla Rahmah Febrianti; Erma Setiawati (Jurnal Akuntansi dan Pajak, 2025)
Capital structure is a comparison between total debt and capital itself. This research aims to analyze the determination of factors that influence the capital structure of industrial sector companies listed on the Indonesia Stock Exchange in 2021-2023. The sampling technique used in this research was purposive sampling and 57 samples of observation data were obtained, using the SPSS version 2025 program. The analytical method used was multiple linear regression analysis. The research results provide empirical evidence that profitability, liquidity and asset structure influence capital structure. Meanwhile, company size and sales growth have no effect on capital structure.